Adsorption Behavior of Heavy Metal Ions by Hybrid Inulin-TEOS for Water Treatment - Wan Norfazilah Wan Ismail; Mohamad Irfan Arif Irwan Syah; Nur Hanisah Abd Muhet; Nurul Hidayah Abu Bakar; Hartina Mohd Yusop; Nurlin Abu Samah (Civil Engineering Journal, 2022)
The present work reports the adsorption behavior involved in the adsorption of heavy metal ions using a hybrid inulin-tetraethoxysilane (TEOS) adsorbent produced through the sol-gel process. An aqueous multi-element solution was used in order to examine the inulin-TEOS adsorbent efficiency in removing Cd2+, Co2+, and Ni2+ ions. The effects of the contact duration, adsorbent dosage, initial concentration, and solution pH on the adsorption of the targeted metal ions in batch systems were evaluated. The optimal conditions for the removal of all targeted heavy metals were as follows: 30 mg of an adsorbent dosage at pH 4 and 5 minutes of contact time with an initial concentration of 0.5 mg/L. A one-way analysis of variance (one-way ANOVA) with a replication test showed that all parameters had significant differences at a p-value of 0.05. At the optimum condition, 92.59%, 90.27%, and 86.472% of Cd2+, Ni2+, and Co2+ were removed, respectively. Findings from kinetic studies suggest that the pseudo-second order model can successfully describe the overall adsorption process. Additionally, the adsorption process can be adequately explained using an intra-particle diffusion model with diffusion rate constants following the sequence of Kint,1 > Kint,2 for Co2+ and Ni2+ and Kint,1 > Kint,2 > Kint,3 for Cd2+ in each step. The results suggest that Ni2+ fits with the Langmuir isotherm, while Cd2+ and Co2+ better fit the Freundlich one. Finally, the adsorbent can be reused and is able to retain a good percentage of removal, with percentage difference decreases of 1.99%, 3.29%, and 4.12% for Cd2+, Ni2+, and Co2+, respectively, after the fifth cycle. The hybrid inulin-TEOS bio-sorbent has good adsorption capacity and durability, which could offer a low-cost practical cleaner production process for removing targeted analytes from wastewater. Doi: 10.28991/CEJ-2022-08-09-03 Full Text: PDF